An Economic Philosophy of Production, Work and Consumption A Transhistorical Framework - Edvinsson, Rodney (Routledge Studies in the History of Economics, 2023)
An Economic Philosophy of Production, Work and Consumption presents a new transhistorical framework of defining production, work and consumption. It shows that they all share the common feature of intentional physical transformation of something external to the agent, at some point in time. The book opens with a discussion of various theoretical traditions within economics, spanning mainstream and heterodox perspectives, and problems with production definitions in use today. Next, the author outlines various definitions in a more formal manner and provides a discussion on measurement and the production boundary. Unproductive work is redefined as socially reproductive, i.e. such that would not be performed on a Robinson Crusoe Island. Finally, the volume applies the new conceptual framework to various historical cases and discusses the future of production, work and consumption. This essential volume will be of interest to scholars of economic philosophy and methodology, the history of economic thought, economic history and national accounting.